Determination of the cellulolytic activity of Micromycetes by an express method - Zeltina, M O; Leite, M P; Apine, A J; Bariss, U A; Shvinka, J E (Folia microbiologica, 1991)
An express method of testing the cellulolytic activity of Trichoderma viride in media with cellulose-containing substrates by the rate of glucose production has been elaborated. The optimum temperature selections and duration of sample incubation (1 h, 50 degrees C) have been described, and the temperature coefficient for the scale-down of the enzyme complex from 50 to 30 degrees C (0.77) has been determined.
Keywords: Cellulase; Culture Media; Hydrolysis; mykologie; celulasa; Mycology; hydrolýza; Trichoderma; kultivační média